2016
DOI: 10.3233/jad-150283
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease

Abstract: Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Moreover, in a Parkinson's disease model, Cx43 immunoreactivity was elevated in astrocytes, glial cells and the methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-lesioned striatum [30]. We also demonstrated previously that the level of Cx43 was upregulated in prion disease models, but the exact mechanism of such overexpression has not been elucidated [33]. These results clearly indicate the involvement of Cx43 in the pathophysiology of various tissue conditions.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Moreover, in a Parkinson's disease model, Cx43 immunoreactivity was elevated in astrocytes, glial cells and the methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-lesioned striatum [30]. We also demonstrated previously that the level of Cx43 was upregulated in prion disease models, but the exact mechanism of such overexpression has not been elucidated [33]. These results clearly indicate the involvement of Cx43 in the pathophysiology of various tissue conditions.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study demonstrated that overexpression of the disease-associated mutants of PrP C (P102L and MΔ8) impaired neuronal differentiation because of the failure to inactivate RhoA/ROCK and reduced the coimmunoprecipitation of RhoA and p190RhoGAP in PC12 cells [17,18]. In addition, scrapie infection upregulated the expression of Cx43 through the JNK signaling pathway in both in vitro and in vivo models of prion disease [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations